Water management indicators - State of the art for the Mediterranean Region - Lutter S.; Schnepf D. (Dialogues on Mediterranean water challenges: Rational water use, water price versus value and lessons learned from the European Water Framework Directive, 2011)
In the Mediterranean region physical water scarcity is an important issue, and consequently the management of water resources is of great relevance, in order to achieve sustainable development. However, big challenges in water management and the perception that current water management models do have deficits in integrating the views of important key stakeholders have increased the (especially international) pressure for implementing actions towards Integrated Water Resources Management (IWRM). As a consequence, an increasing interest in water resource assessment and water management indicators can be observed. This paper discusses existing water management indicators sets - SWAP, Aquastress Water Stress Index and UN Water - Water monitoring - with respect to their applicability in the Mediterranean region. For this purpose, the authors' perceptions were complemented with the knowledge of a group of experts which contributed by means of expert interviews. The main conclusion of the analysis is that so far no indicator set tailored for the Mediterranean has been developed. To develop the best-suited set a participatory, integrative and iterative process needs to be set up. The present paper constitutes the first iteration step in this process.
3. MELIA Workshop Water Value Impacts on the Mediterranean Water Policies, 2009/03/21-23, Istanbul (Turkey); 4. MELIA Workshop Benchmarking Exercise and Recommendations on the Application of the Water Framework Directive, 2010/03/21-26, Amman (Jordan)